The formal disciplines theory and mental logic (2016)
(Eng) The formal discipline theory claims that the study of mathematics develops individuals’ logical skills. Attridge and Inglis carried out an experiment in order to check whether or not that theory holds. Their conclusion was that their results showed that, while mathematics can indeed improve logical abilities, it is necessary to assume the defective interpretation of conditional. However, López-Astorga countered that other interpretations of their results are possible, that they do not prove that the material interpretation of conditional is not valid, and that the mental models theory can also explain them. In this paper, I comment the problems linked to the other possible interpretations proposed by López-Astorga and try to argue that the best option in the interpretation of Attridge and Inglis’ results is to assume the mental logic theory.